Territorial standards for innovation : analysis for the regions of Portugal - Natário, Maria Manuela (2020)
Competitiveness among regions and innovation dynamics are intimately related and depend on a solid and effective innovation system. This study aims to measure innovativeness in different Portuguese regions and to evaluate the nature of the innovation process and the relationship between innovativeness and its region of origin. To characterize the territorial innovation processes and to identify innovation patterns by regions, it analyzes their main distinctive factors, based on the Community Innovation Survey results for each region. Thus, it compares the Portuguese regions by verifying the existence of subjacent clusters and finding out the characteristics that distinguish the different groups of regions. The results point to the existence of four groups of regions, and the factors identified are related to the innovation process, namely objectives of innovation, sources of innovation, collaborative networks, triple helix performance, and obstacles to innovation.